Weak Link of University Library: Knowledge Protection and Reader Protection - Srikonda, Khalid Ramesh (Journal of Social Science and Humanities, 2025)
Academic libraries are treasuries of knowledge and information, yet they face threats and vulnerabilities that disrupt the library environment, affecting both staff and users. This article explores these academic library threats and suggests strong protective measures. Various issues, such as theft, mutilation, and cybercrimes, pose distinctive threats. Theft compromises resources and educational experiences, while cybercrimes imperil digital assets and sensitive data. To mitigate these challenges, preventive tactics involve security, staff training, user education, and cybersecurity. Security systems like surveillance and access controls fortify physical protection. Staff training ensures informed responses to security threats, while user education cultivates vigilance and shared responsibility. Cybersecurity safeguards digital resources and user data. The article primarily aims to identify vulnerabilities in academic libraries, raise awareness, promote best practices, and encourage collaborative efforts among librarians and security personnel.